The analysis of legal cases - Di Donato, Flora (Law, language and communication, 2019)
This book examines the roles played by narrative and culture in the construction of legal cases and their resolution.It is articulated in two parts. Part I recalls epistemological turns in legal thinking as it moves from theory to practice in order to show how facts are constructed within the legal process. By combining interdisciplinary paradigms and methods, the work analyses the evolution of facts from their expression by the client to their translation within the lawyer-client relationship and the subsequent decision of the judge,focusing on the dynamic activity of narrative construction among the key actors: client, lawyer and judge.Part II expands the scientific framework toward a law-and-culture-oriented perspective, illustrating how legal stories come aboutin the fabric of the authentic dimensions of everyday life. The book stresses the capacity of laypeople, who in this activityare equated with clients, to shape the law, dealing not just with formal rules, but also with implicit or customary rules, in given contexts. By including the illustration of cases concerning vulnerable clients, it lays the foundations for developing a socio-clinical research programme, whose aims including enabling lay and expert actors to meet for the purposes of improving forms of collective narrations and generating more just legal systems